The European Horticulture Market : Opportunities for Sub-Saharan African Exporters - Labaste, Patrick (Washington, DC: World Bank, 2012)
Trade is an essential driver for sustained economic growth, and growth is necessary for poverty reduction. In Sub-Saharan Africa, where three-fourths of the poor live in rural areas, spurring growth and generating income and employment opportunities is critical for poverty reduction strategies. Seventy percent of the population lives in rural areas, where livelihoods are largely dependent on the production and export of raw agricultural commodities such as coffee, cocoa, and cotton, whose prices in real terms have been steadily declining over the past decades. The deterioration in the terms of trade resulted for Africa in a steady contraction of its share in global trade over the past 50 years. Diversification of agriculture into higher-value, non-traditional exports is seen today as a priority for most of these countries. Some African countries-in particular, Kenya, South Africa, Uganda, Côte d'Ivoire, Senegal, and Zimbabwe-have managed to diversify their agricultural sector into non-traditional, high-value-added products such as cut flowers and plants, fresh and processed fruits and vegetables. To learn from these experiences and better assist other African countries in designing and implementing effective agricultural growth and diversification strategies, the World Bank has launched a comprehensive set of studies under the broad theme of "Agricultural Trade Facilitation and Non-Traditional Agricultural Export Development in Sub-Saharan Africa." This study provides an in-depth analysis of the current structure and dynamics of the European import market for flowers and fresh horticulture products. It aims to help client countries, industry stakeholders, and development partners to get a better understanding of these markets, and to assess the prospects and opportunities they offer for Sub-Saharan African exporters.